Does Lack of Health Insurance Mediate the Relationship Between Employment Hardships and Unmet Health Care Needs Among Single Mothers?. (November 2017) - Wu, Chi-Fang; Eamon, Mary Keegan; Wang, Ming-Sheng
Using data from a national sample of 451 single mothers collected 24 months during and after the Great Recession, this study tested four hypotheses related to comprehensive measures of employment problems, number of months without health insurance, and unmet medical or dental needs. The results indicate positive relationships between employment problems and unmet medical or dental needs, employment problems and lacking health insurance, and lacking health insurance and unmet medical or dental needs. Most important, lack of health care coverage significantly reduced the relationships between unemployment (by 26%) and underemployment (by 56%) and unmet medical or dental needs. These results indicate that lack of health insurance at least partially mediates the effects of employment problems on single mothers experiencing an unmet medical or dental need. The findings have implications for these mothers' medical and dental care access, which are discussed within the context of the recent health care reforms.